2014
DOI: 10.1016/j.biomaterials.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A nanocarrier system for the delivery of nucleic acids targeted to a pancreatic beta cell line

Abstract: Pancreatic β cells secrete insulin in response to glucose levels and thus are involved in controlling blood glucose levels. A line of pancreatic β cells "MIN6" has been used in studies related to the function of β cells and diabetes therapy. Regulating gene expression in MIN6 cells could accelerate these studies, but an efficient method for the transfection of nucleic acids targeted to MIN6 cells is required. We report here on a liposome-based carrier targeted to pancreatic β cells (Multifunctional envelope-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…b), probably because the ζ ‐potential likely reached a plateau when a certain amount of IgG became bound to the liposomal surface. Furthermore, a previous report showed that the cellular uptake of R8‐modified liposome itself was much higher than that of R8‐unmodified liposomes in the case of HeLa cells . On the basis of our results and findings of previous reports, it can be concluded that R8 assists both the loading of IgG on the liposomal surface and the cellular uptake of the carriers, thus resulting in the efficient cellular internalization of antibodies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…b), probably because the ζ ‐potential likely reached a plateau when a certain amount of IgG became bound to the liposomal surface. Furthermore, a previous report showed that the cellular uptake of R8‐modified liposome itself was much higher than that of R8‐unmodified liposomes in the case of HeLa cells . On the basis of our results and findings of previous reports, it can be concluded that R8 assists both the loading of IgG on the liposomal surface and the cellular uptake of the carriers, thus resulting in the efficient cellular internalization of antibodies.…”
Section: Discussionsupporting
confidence: 78%
“…). We examined the effects of the following inhibitors: amiloride, a specific inhibitor of macropinocytosis by inhibiting the Na/H exchange required for macropinocytosis, a hypertonic medium containing sucrose to specifically inhibit clathrin‐mediated endocytosis through the dissociation of the clathrin lattice, and Fillipin III to specifically inhibit caveolar uptake via the depletion of cholesterol …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the β-MEND has the potential as an efficient nucleic acids delivering system targeted for efficient internalization in MIN6 for application in research and therapy based treatments of diabetes [72].…”
Section: Other Diseasesmentioning
confidence: 99%
“…The most common treatments for cancer are a) surgery, b) chemotherapy, c) radiation therapy, and d) targeted therapy. antisense therapeutic research [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Currently, over a hundred oligonucleotides are in clinical trials from 30 different pharmaceutical companies [23].…”
Section: Editorialmentioning
confidence: 99%